Pengaruh Pengalaman Kerja, Tingkat Pendidikan, Dan Pelatihan Kerja Terhadap Kinerja Karyawan Generasi Z Di Bandar Lampung - Lestari Anggraini; Kemala Puji; Emi Suwarni (STIE AMKOP, 2023)
This study aims to determine the effect of work experience, education level, job training on employee performance. The number of samples in this study were 100 employees with data collection using research instruments, data analysis was quantitative/statistical in nature with the aim of testing the established hypotheses. The sampling method used in this study is a nonprobability sampling method using a purposive sampling technique in which the sampling is based on the criteria determined by the researcher. The results show that work experience, level of education and job training have a positive and significant effect on employee performance in Generation Z. Increasing work experience, level of education and job training will increase employee performance. Keywords: Work Experience, Education Level, Job Training and Employee Performance